Z dziejów rzymskich caligae - Budzanowska-Weglenda, Dominika (In Gremium. Studies in History, Culture and Politics, 2024)
Of the history of Roman caligae For the military successes of the Roman army, the roads and armaments of soldiers were important. Characteristic for Roman legionnaires were their sandals, caligae, cut from one piece of leather, tied with a strap. They had a thick, studded sole, made of three layers of leather. In winter, they were insulated with fabric or fur. About the appearance and meaning of caligae provide, among others Roman literature and sculptures. From caligae comes the nickname of Emperor Caligula.